Ultrasound stimulation of the vagus nerve as a treatment modality for anxiety - Goyal, Michell; Goyal, Ravi; Sanguinetti, Joseph L. (Frontiers in Psychiatry, 2024)
Anxiety is an increasingly prevalent mental disorder causing widespread hardship and interfering with society’s economic progression. Standard treatments include various talk therapies with poor prognoses or drug interventions with complex side effects, both introducing unnecessary burdens to patients. To remedy this, noninvasive ultrasound stimulation to the vagus nerve is a novel, low-cost treatment that is showing promise. Although vagus nerve stimulation is already approved for epilepsy and other conditions, it requires regular maintenance. In contrast, studies using noninvasive ultrasound stimulation have shown preliminary positive results in affecting vagal activity with minimal drawbacks. This review covers a variety of studies investigating the effects of ultrasound stimulation on the vagus nerve. With rising levels of anxiety with each generation, there is a pressing need for more innovative and diverse treatments with fewer costs and more benefits.